2010
DOI: 10.1007/s11250-010-9673-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of (co)variance components and genetic parameters for growth traits in Sirohi goat

Abstract: Data were collected over a period of 21 years (1988-2008) to estimate (co)variance components for birth weight (BWT), weaning weight (WWT), 6-month weight (6WT), 9-month weight (9WT), 12-month weight (12WT), average daily gain from birth to weaning (ADG1), weaning to 6WT (ADG2), and from 6WT to 12WT (ADG3) in Sirohi goats maintained at the Central Sheep and Wool Research Institute, Avikanagar, Rajasthan, India. Analyses were carried out by restricted maximum likelihood, fitting six animal models with various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
32
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 29 publications
15
32
9
Order By: Relevance
“…High positive direct genetic correlations were estimated among WW, W8, W12 and W16. Similar correlations were obtained among early body weights for other goat breeds (Bosso et al, 2007;Boujenane & Hazzab, 2008;Zhang et al, 2008;Gowane et al, 2011;Rashidi et al, 2011). The maternal genetic correlations obtained between birth weight and the other body weights were medium to high.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…High positive direct genetic correlations were estimated among WW, W8, W12 and W16. Similar correlations were obtained among early body weights for other goat breeds (Bosso et al, 2007;Boujenane & Hazzab, 2008;Zhang et al, 2008;Gowane et al, 2011;Rashidi et al, 2011). The maternal genetic correlations obtained between birth weight and the other body weights were medium to high.…”
Section: Resultssupporting
confidence: 75%
“…No other r am estimates are available in the literature for any traits in Angora goats. Negative correlations were also reported for early body weight in Boer goats (Zhang et al, 2008), Draa goats (Boujenane & Hazzab, 2008), Sirohi goats (Gowane et al, 2011) and Markhoz goats (Rashidi et al, 2011). However, conflicting estimates, pertaining to sign and magnitude, were reported for a wide range of sheep breeds, as summarised by Safari & Fogarty (2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low to moderate estimates of genetic correlation between the birth and weaning weight were documented by some researchers [12][13][14][15][16][17][18][19][20][21][22][23]. Low phenotypic correlation as found in present study between the two traits were also reported by different researchers [12,17,20,24].…”
Section: Birth Weight and Weaning Weightsupporting
confidence: 75%
“…Moderate genetic correlations between the two traits were also reported by many other workers in different goat breeds around the world [9,17,19,22].…”
Section: Birth Weight and Six Month Weightsupporting
confidence: 59%